Climate adaptation of pre-Viking societies. (15th February 2022) - Bajard, Manon; Ballo, Eirik; Høeg, Helge I.; Bakke, Jostein; Støren, Eivind; Loftsgarden, Kjetil; Iversen, Frode; Hagopian, William; Jahren, Anne H.; Svensen, Henrik H.; Krüger, Kirstin
Abstract: Understanding how the Viking societies were impacted by past climate variability and how they adapted to it has hardly been investigated. Here, we have carried out a new multi-proxy investigation of lake sediments, including geochemical and palynological analyses, to reconstruct past changes in temperature and agricultural practices of pre-Viking and Viking societies in Southeastern Norway during the period between 200 and 1300 CE. The periods 200–300 and 800–1300 CE were warmer than the 300–800 CE period, which is known as the "Dark Ages Cold Period". This cold period was punctuated by century-scale more temperate intervals, which were dominated by the cultivation of cereals and hemp (before 280 CE, 420–480 CE, 580–700 CE, and after 800 CE). In between, cold intervals were dominated by livestock farming. Our results demonstrate that the pre-Viking societies changed their agricultural strategy in response to climate variability during the Late Antiquity. Graphical abstract: Image 1 Highlights: Record of temperature and agricultural practices from the same lake sediment archive. The period 300–800 CE was colder than 200–300 CE and 800–1300 CE in SE Norway. Phases dominated by grazing are synchronous with colder intervals during 300–800 CE Phases dominated by cultivation are synchronous with warm intervals during 300–800 CE Pre-Viking societies changed their way of living to adapt to the climate variability.